Antibacterial activity and mannosylerythritol lipids against vegetative cells and spores of Bacillus cereus. (December 2019) - Shu, Qin; Niu, Yongwu; Zhao, Wenjun; Chen, Qihe
Abstract: This study aimed to investigate the antibacterial activity and underlying mechanism of mannosylerythritol lipids (MELs) against vegetative cells and spores of Gram-positive Bacillus cereus . The minimum inhibitory concentration and minimum bactericidal concentration of MELs was 1.25 mg/mL and 2.50 mg/mL, respectively. The growth curve assay and survival rate also showed that MELs had great antibacterial effect . The analysis data of intracellular constituent leakage and cell viability demonstrated MELs damaged the integrity of cell membrane . By scanning electron microscope and transmission electron microscope, the treated bacterial cells exhibited apparent morphological and ultrastructural changes, further affirming the disruption of cell membrane and the unbalance of cellular environments. Furthermore, MELs has showed good ability to inhibit the germination of B. cereus spores. The findings suggested that MELs acted its antibacterial effect primarily by means of membrane disruption, and indicating it will be alternatives to antibacterial agents and preservatives applied into food processing. Highlights: Mannosylerythritol lipids had strong antibacterial activity against Bacillus cereus. Mannosylerythritol lipids damaged the cell membrane of Bacillus cereus. Mannosylerythritol lipids had inhibitory effect on germination of Bacillus cereus spores.